Diurnal variations in physical performance: Are there morning-to-evening differences in elite male handball players? - Pavlovic, L.; Stojiljkovic, N.; Aksovic, N.; Stojanovic, E.; Valdevit, Z.; Scanlan, A. T.; Milanovic, Z. (Journal of Human Kinetics, 2018)
The purposes of this study were to determine: 1) morning-to-evening differences in physical performance with and without a ball; and 2) associations between sleep outcomes (duration and quality) and physical performance in handball players. Sixteen elite, male handball players (25.4 ± 5.8 yr, 94.0 ± 7.4 kg, 193.5 ± 7.5 cm) completed physical performance tests without a ball (a zig-zag test assessing agility, linear sprints, and countermovement (CMJ) and squat jumps) and with a ball (a zig-zag test and linear sprints) in the morning and evening. In addition, sleep quality and quantity during the night before testing were obtained using self-reported measures. Superior physical performance was evident in all tests during the evening compared to the morning hours (p < 0.003). Specifically, jump height was moderately (ES = 0.73 to 1.02) higher during the evening. Similarly, moderate (ES = 1.17) and large (ES = 1.67) improvements in zig-zag test performance were apparent during the evening with and without the ball, respectively. Also, large to very large (effect size (ES) = 1.29 to 2.09) differences were evident between sessions for sprint performance with and without the ball. No significant correlations (p > 0.05) were apparent between sleep duration and quality and physical performance in both the morning and evening sessions. Diurnal variations in physical performance were apparent in elite male handball players with enhanced performance with and without the ball in the evening compared to morning hours. These findings indicate that morning-to-evening differences in physical performance should be considered when developing conditioning plans or preparing for competition in handball.